2018
DOI: 10.1093/gji/ggy135
|View full text |Cite
|
Sign up to set email alerts
|

Induced seismicity at the UK ‘hot dry rock’ test site for geothermal energy production

Abstract: In enhanced geothermal systems (EGS), fluid is injected at high pressure in order to stimulate fracturing and/or fluid flow through otherwise relatively impermeable underlying hot rocks to generate power and/or heat. The stimulation induces micro-earthquakes whose precise triggering mechanism and relationship to new and pre-existing fracture networks are still the subject of some debate. Here we analyse the dataset for induced micro-earthquakes at the UK "hot dry rock" experimental geothermal site (Rosemanowes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…which SI values are available is the Rosemanowes Hot Dry Rock geothermal site, for which Li et al (2018) found maximum values of SI = -3.4, significantly lower than the values found for PNR-1z.…”
Section: Seismic Efficiency and Seismogenic Indexmentioning
confidence: 66%
“…which SI values are available is the Rosemanowes Hot Dry Rock geothermal site, for which Li et al (2018) found maximum values of SI = -3.4, significantly lower than the values found for PNR-1z.…”
Section: Seismic Efficiency and Seismogenic Indexmentioning
confidence: 66%
“…Temperatures at the base of UD-1 have been predicted at about 200°C (Ledingham et al, 2019). Shearing and downward flow of injected fluid was observed in boreholes as part of the earlier HDR project and tracked with measured microseismicity (Pine & Batchelor, 1984;Green et al, 1988;Li et al, 2018). Figure 10 shows a map of SW England overlain with seismicity data from the BGS (Musson, 1996).…”
Section: Porthtowan Fault Zone In Cornwall Ukmentioning
confidence: 76%
“…Temperatures at the base of UD-1 were predicted to be about 200 • C (Ledingham et al, 2019), and recent observations confirm this (Reinecker et al, 2021). Shearing and downward flow of injected fluid was observed in boreholes as part of the earlier HDR project and tracked with measured microseismicity (Pine and Batchelor, 1984;Green et al, 1988;Li et al, 2018).…”
Section: Porthtowan Fault Zone In Cornwall Ukmentioning
confidence: 85%